QURANIC CONCEPT OF MULTIPLE INTELLIGENCE (ULUL ALBAB): AN ANALYSIS OF VERSES FROM SURAH AL-BAQARAH: 177-188 - Tazul Islam (International Prophetic Conference (SWAN) FPQS USIM, 2024)
This paper aims to present the Quranic concept of multiple intelligence. To this end, it has selected some verses from the second chapter of the Quran that highlight the concept of Ulul albab. It explores how this concept manifests multiple intelligence according to the framework of theory of intelligence and learning domains. The methodological framework applied as follows: categorization of themes in the selected verses; analysing the themes; exploring the character traits of Ulul Albab according to moral, intellectual, social, and spiritual virtues; application of Ulul Albab traits to multiple intelligences: according to IQ (Intellectual Intelligence), EQ (Emotional Intelligence), and SQ (Spiritual Intelligence); application of Bloom’s learning domains for Ulul Albab traits to translate the concepts of Ulul Albab into actionable classroom activities that progressively build students' knowledge, emotional engagement, and skills across the three domains: Cognitive, Affective, and Psychomotor. The outcome of this process shows that Ulul albab’s traits strongly indicate to multiple intelligence. However, this study is limited to only one group of sixteen groups of verses where the term Ulul albab is mentioned. Further studies can be extended to all groups of verses to conclude a general conclusion on whether Ulul albab represents multiple intelligence or not.